Theory of key polynomials - Moraes, Michael Willyans Borges de (2022)
There is a central question on valuation theory: given a rank one valuation on a field K, what can we talk about of an extension of to the polynomial ring K[X]? The theory of key polynomials is an approach to treat exactly this issue.